Social Attitude and Community Participation on Flood Prevention Natural Disaster - Sri Yuni Murti Widayanti (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2016)
The research on social attitude and community partcipation on the floods prevention aimed to describe community’s knowledge. Social attitude, and participation toward floods victims prevention and also the implementation of post-floods social rehabilitation. The research was conducted in the district of North Lampung, Lampung Province. Data were collected from various sources, such as documentation , in-depth interview, and observation. Through descriptive qualitative analysis, the results revealed that community’s knowledge and understanding about floods were quite high, so the floods prevention which was conducted by the social agencies and related social institutions were more effective in reducing the impact of floods. People tried to find social rehabilitation assistance for the flood victims. The proposed recommendation was there should be mitigation efforts towards floods prevention through regional regulation which regulates spacial building, implementation and enforcement of legislation on safety land use, as well as the development of the village disaster alert program that will be used to coordinating participation of community, improving the system of agriculture and socialization to the society about the causes and effects of floods,